Pengembangan Sistem Informasi Pengarsipan Surat Berbasis Web pada Bidang Hukum, Kepegawaian, dan Umum Dinas Pendidikan Aceh: Information System - Ismail; Alfina; Harry Idwan (Jurnal Sistem Komputer (SISKOM), 2026)
The management of letters in the Legal, Personnel, and General Affairs Division of the Aceh Education Office is still carried out manually, causing several issues such as slow archive retrieval, risk of recording errors, and potential document loss. These conditions reduce the effectiveness of administrative processes. This study aims to design a web-based letter archiving information system to improve archive management so it becomes faster, more organized, and more accurate. The system was developed using the waterfall method, which includes requirement analysis, system design, implementation, and testing stages. The system is built using PHP programming language and MySQL database to support centralized data storage. Main features include login with user role separation, incoming letter data management, search by agenda number or letter number, data editing, report generation, and logout. Testing results show that all functions run according to design, including data input, search, update, and deletion processes. The system is also able to provide validation for user input errors. The use of a web-based system improves work efficiency, speeds up administrative processes, and ensures accuracy and neatness in letter archive management within the institution.